Aspect-Based Sentiment Analysis of Jkn Mobile Application Reviews Using the Random Forest Method and Information Gain as Feature Selection - Dwiputra Harta, Yauw James Fang; Wibawa, I Gede Arta; Karyawati, Anak Agung Istri Ngurah Eka; Mogi, Komang Ari (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 1 (2024): JELIKU Volume 13 No 1, August 2024DO - 10.24843/JLK.2024.v13.i01.p06, 2024)
In the rapidly advancing digital age, applications have become integral to daily life. This study focuses on aspect-based sentiment analysis of reviews for the Mobile JKN application using the Random Forest and Information Gain methods. This technological approach is vital for understanding user opinions, guiding further improvements and developments. Google Play Store review data is employed, with rating scores serving as guides for sentiment classification. The study aims to provide in-depth insights into sentiments and aspects influencing Mobile JKN application reviews. Through this approach, the quality of healthcare services delivered via the application is anticipated to be continually enhanced.